2005
DOI: 10.1016/j.destud.2004.09.006
|View full text |Cite
|
Sign up to set email alerts
|

The (in)secure position of the design jury towards computer generated presentations

Abstract: The tendency towards computer aid in design presentations differs in academia than in the practicing field; practice seems to welcome computer aid in presentation, whereas in academia there seems to be a dilemma. In this study, we approach this duality based on our teaching experience within an interior architecture curriculum. First, we unfold the problematic to identify the contributing factors, then we observe the tendencies through a questionnaire with design students and interviews with design instructors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 6 publications
0
9
0
1
Order By: Relevance
“…(Salman et al, 2014). Ceci peut causer une frustration dans le cas où les étudiants ou les enseignants ne maitrisent pas très bien ces logiciels (Basa & Şenyapili, 2005). Et si la fixation sur la première idée chez l'étudiant devient plus dominante , cela peut le rendre résistant à la réflexion sur les propositions de l'enseignant, ce qui limite prématurément l'espace de design et restreint la nouveauté (Jansson & Smith, 1991).…”
Section: La Réussite D'un Enseignement Selonunclassified
“…(Salman et al, 2014). Ceci peut causer une frustration dans le cas où les étudiants ou les enseignants ne maitrisent pas très bien ces logiciels (Basa & Şenyapili, 2005). Et si la fixation sur la première idée chez l'étudiant devient plus dominante , cela peut le rendre résistant à la réflexion sur les propositions de l'enseignant, ce qui limite prématurément l'espace de design et restreint la nouveauté (Jansson & Smith, 1991).…”
Section: La Réussite D'un Enseignement Selonunclassified
“…A third faculty member held degrees in journalism and technical writing; within these academic programs, computer-produced products commonly were critiqued and assessed through a jury-like process. Indeed, where computer-produced products are created, juried approaches to assessment are common (see, for instance, Basa & Şenyapılı, 2005). Because three out of six faculty members had familiarity with juries, the idea for juries was privileged with a type of cultural capital that pushed their use forward as an appropriate innovation within the IDT program.…”
Section: Conceptualizing Products and Processes For Juriesmentioning
confidence: 99%
“…While its time and energy saving nature has better accommodated its integration in design practice (Sanders, 1996), research also identified limitations of CAD technology. Specifically, they require technical proficiency for production (Basa & Şenyapth, 2005), yet, computer renderings often appear sterile. Further, they may provide unnecessary information (Pable, 2006).…”
Section: Development Of Digital Tools Within Interior Designmentioning
confidence: 99%
“…Reflecting the increasing interest in mixed use or hybrid design approach , most studies on design tools within design professions focused on either digital technology only (Gibson, 2007; Lee, 2009; Lyon et al., 2008; McConnell & Waxman, 1999; McLain‐Kark, 2000; Seidler, 2009) or conducted comparative analysis between hand and digital media (Basa & Şenyapth, 2005; Brandon & McLain‐Kark, 2001; North & Miller, 2002; Pable, 2006). In addition, some research has integrated hand and digital methods in design education (Dorta et al., 2008; Kim, 2008).…”
Section: The Hybrid Approach In Contemporary Interior Design Professionmentioning
confidence: 99%
See 1 more Smart Citation